2022
DOI: 10.3389/fnut.2022.849314
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Dietary and Lifestyle Responses After COVID-19 Vaccine Availability in Selected Arab Countries

Abstract: BackgroundThe COVID-19 pandemic has been consistently associated with unhealthy lifestyle behaviors and dietary practices. This study aimed to assess the dietary and lifestyle behaviors of adults after COVID-19 vaccine availability and their attitude toward the vaccine in selected Arab countries.MethodsA cross-sectional survey-based study was conducted between October 2021 and December 2021 using Google Forms (n = 2259). A multi-component questionnaire was used to collect socio-demographic characteristics, att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…Likewise, a study conducted during the lockdown in the UAE reported a high prevalence of unhealthy lifestyle behaviors among the UAE residents [ 19 ]. This effect remained unchanged after the availability of the COVID-19 vaccine [ 20 ] and it persists in the results of our current study.…”
Section: Discussionsupporting
confidence: 80%
“…Likewise, a study conducted during the lockdown in the UAE reported a high prevalence of unhealthy lifestyle behaviors among the UAE residents [ 19 ]. This effect remained unchanged after the availability of the COVID-19 vaccine [ 20 ] and it persists in the results of our current study.…”
Section: Discussionsupporting
confidence: 80%
“…Another study by Cheikh Ismail et al showed that almost one in three people in the UAE reported weight gain during the COVID-19 pandemic, concurrently with reports of unhealthy eating patterns, lower physical activity levels, and increased screen time [ 70 ]. In addition, a follow-up study in four Arab countries, including the UAE, indicated that several unfavorable lifestyle and dietary habits persisted even after the availability of the COVID-19 vaccine, indicating that people might have continued with eating habits acquired during the COVID-19 lockdown [ 71 ]. One recent study found that smoking was significantly associated with high BMI in university students in both Dubai and Palestine [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cheikh et al also reported that close to 40% of the Lebanese participants in their study were not consuming fruits and vegetables on a daily basis [ 31 ], while Dimassi et al reported a significant increase in consumption of fruits and vegetables [ 32 ]. Nevertheless, as a result of the pandemic, almost 40% of the participants have reported weight gain almost [ 33 ]. Unhealthy dietary patterns and weight gain are especially problematic during a pandemic since healthy dietary habits are the cornerstone to enhanced immunity, which could help ward of the severe consequences of viruses [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was an interesting finding in our study, as over a third of the individuals reported increasing their intake of fruits, vegetables, and grains. Weight gain is more likely to occur when food intake is increased while physical activity levels decline, as is often the case during lockdowns [ 33 , 43 ]. Although we did not assess physical activity using validated tools, similar studies have found that physical activity levels often fall during lockdown [ 43 ].…”
Section: Discussionmentioning
confidence: 99%